The Influence Of Visual Appearance And Technology Reliability On Website Quality Through User Experience (UX): An Empirical Study Of Online Tryout Users - Arthus D. Larumu; Surya Danang; Paske Victory Modaso (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effect of visual appearance and technology reliability on website quality through user experience (UX) as a mediating variable. This research uses a quantitative approach with a survey method, where data is collected through a questionnaire to 250 respondents who use the online tryout platform. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that visual appearance and technological reliability have a positive and significant influence on user experience (UX) and website quality. In addition, user experience (UX) is proven to mediate the relationship between visual appearance and technology reliability with website quality. The recommendation from this study is that website developers need to focus on improving visual design and technology in order to provide a better user experience.